A study of mixing and intermittency in a coaxial turbulent jet - Ranga Dinesh, K. K. J.; Savill, Mark A.; Jenkins, Karl W.; Kirkpatrick, M. P. (Elsevier Science B.V., Amsterdam., 2010)
A large eddy simulation study of mixing and intermittency of a coaxial turbulent jet discharging into an unconfined domain has been conducted. The work aims to gain insight into the mixing and intermittency of turbulent coaxial jet configurations. The coaxial jet considered has relatively high jet velocities for both core and annular jets with an aspect ratio (core jet to annular jet) of 1.48. The computations resolved the temporal development of large-scale flow structures by solving the transport equations for the spatially filtered mass, momentum and passive scalar on a non-uniform Cartesian grid and employed the localized dynamic Smagorinsky eddy viscosity as a sub-grid scale turbulence model. The results for the time-averaged mean velocities, associated turbulence fluctuations and mean passive scalar fields are presented. The initial inner and outer potential cores and the shear layers established between two cores have been resolved, together with the establishment of high turbulence regions between the shear layers. The passive scalar fields developing from the core and the bypass flow were found to exhibit differences at near and far field locations. Probability density distributions of instantaneous mixture fraction and velocity have been created from which intermittency has been calculated and the development of intermittency from the probability density distributions for instantaneous velocity follows similar variations as for the passive scalar fields.
Keywords: large-eddy simulation probability density-function near-field passive scalar initial region flows model